VGluT1(+) Neuronal Glutamatergic Signaling Regulates Postnatal Developmental Maturation of Cortical Protoplasmic Astroglia - Morel, Lydie (Society for Neuroscience, 2014)
Functional maturation of astroglia is characterized by the development of a unique, ramified morphology and the induction of important functional proteins, such as glutamate transporter GLT1. Although pathways regulating the early fate specification of astroglia have been characterized, mechanisms regulating postnatal maturation of astroglia remain essentially unknown. Here we used a new in vivo approach to illustrate and quantitatively analyze developmental arborization of astroglial processes. Our analysis found a particularly high increase in the number of VGluT1(+) neuronal glutamatergic synapses that are ensheathed by processes from individual developing astroglia from postnatal day (P) 14 to P26, when astroglia undergo dramatic postnatal maturation. Subsequent silencing of VGluT1(+) synaptic activity in VGluT1 KO mice significantly reduces astroglial domain growth and the induction of GLT1 in the cortex, but has no effect on astroglia in the hypothalamus, where non-VGluT1(+) synaptic signaling predominates. In particular, electron microscopy analysis showed that the loss of VGluT1(+) synaptic signaling significantly decreases perisynaptic enshealthing of astroglial processes on synapses. To further determine whether synaptically released glutamate mediates VGluT1(+) synaptic signaling, we pharmacologically inhibited and genetically ablated metabotropic glutamate receptors (mGluRs, especially mGluR5) in developing cortical astroglia and found that developmental arborization of astroglial processes and expression of functional proteins, such as GLT1, is significantly decreased. In summary, our genetic analysis provides new in vivo evidence that VGluT1(+) glutamatergic signaling, mediated by the astroglial mGluR5 receptor, regulates the functional maturation of cortical astroglia during development. These results elucidate a new mechanism for regulating the developmental formation of functional neuron-glia synaptic units.